REFLECTION OF MAQASHID SYARIAH AND ISLAMIC STUDIES ON ECONOMIC DEVELOPMENT TOWARDS A GOLDEN INDONESIA - Mansur, ubaidillah; Nur, Iffatin (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2024)
AbstractAn interdisciplinary-based development economics discourse is a relatively new breakthrough in achieving several dimensions, including: material and spiritual balance, as well as a balance of morality for all stakeholders. It must be realized that the traditional doctrinal style of study is no longer adequate in the study of Islamic economics, so there is a need for integrated (interdisciplinary) scientific disciplinary collaboration in responding to and responding to development economics. Researchers will try to contribute thoughts about development economics based on interdisciplinary studies from a perspective maqashid al-syariah and Islamic studies. To answer this problem, the researcher used library research with a descriptive approach and the data obtained was of course of a descriptive nature Dharuriat by collecting it through content analysis in the form of in-depth discussion. The results of the research are that the implementation of development economics must be based on principles such as tasawwur (worldview), humans are the conceptualizers and actors of development, the nature of the spirit, the world and the afterlife as a sign of time, knowledge as a guide, worship as the basis for development, natural resources as a means, and Allah's blessing as the final goal of development. Meanwhile, the economic concept of development is based on maqashid sharia offered by al-Syathibi is a basic requirement (Daruriyyah), comfort (Hajjiyyah), and luxury (tahsiniyyah). Meanwhile, what Akram offers are five components: wealth stability, wealth investment, community welfare, economic activity and legal ownership.Keywords: Reflection, Maqashid Sharia, Islamic Studies, and Development Economics